THE EFFECTIVENESS OF GOOGLE CLASSROOM IN INCREASING STUDENT UNDERSTANDING AND INTERACTIVITY IN ONLINE LEARNING - Rima Tamara Aldisa; Frenda Farahdinna; Mohammad Aldinugroho Abdullah (Adisam Publisher, 2024)
In the current digital era, the use of online learning platforms such as Google Classroom is becoming increasingly relevant in supporting an effective learning process. This research aims to investigate the effectiveness of Google Classroom in increasing learning interactions and student involvement in learning. The research method used was an experiment with a pretest and posttest design as a group. Data was collected through the results of student engagement questionnaires, observations of learning interactions, and in-depth interviews with students. The results of the research show that the use of Google Classroom significantly increases learning interactions, student understanding in using technology and student engagement compared to conventional learning methods. Students in the experimental group showed increased motivation to learn, participation in class discussions, and collaboration between students. These findings confirm the potential of Google Classroom as an effective supporting tool in improving the quality of learning interactions and student involvement in the learning process. This research provides insight for educators and helps students to better utilize online learning technology in designing and delivering interactive and interesting learning materials.